2017
DOI: 10.1177/0892705717704487
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyurethane dispersion treatment on the performance improvement of carbon woven fabric-reinforced composites

Abstract: In this study, two types of polyurethane dispersion were applied as surface treatment for 10 types of washed/nonwashed carbon plain woven fabric-reinforced thermosetting and thermoplastic composites. To investigate the effects of surface treatment on the mechanical properties, the impregnation of various laminates was observed by a digital microscope. Dynamic mechanical analysis (DMA) was employed to investigate the interfacial interaction properties. Static tensile test was used to study the mechanical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…23,24 The commonly used surface treatment methods are acid oxidation, 25 plasma treatment, 26 rare earth treatment, 27 gamma irradiation, 28 and silane coupling agent treatment. 29 Other treatment methods are laser treatment, 30 chemical grafting, polymer coating, polyurethane dispersion (PUD) sizing, 31,32 stitching, 33 interleaving polymeric nanofibers in interlaminar regions, 34 and synthesizing carbonaceous structures on CFs. 35 Latif et al investigated the effect of silane coupling agent amount on the mechanical properties of vinylester-epoxy hybrid resinbased carbon fiber-reinforced polymers.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 The commonly used surface treatment methods are acid oxidation, 25 plasma treatment, 26 rare earth treatment, 27 gamma irradiation, 28 and silane coupling agent treatment. 29 Other treatment methods are laser treatment, 30 chemical grafting, polymer coating, polyurethane dispersion (PUD) sizing, 31,32 stitching, 33 interleaving polymeric nanofibers in interlaminar regions, 34 and synthesizing carbonaceous structures on CFs. 35 Latif et al investigated the effect of silane coupling agent amount on the mechanical properties of vinylester-epoxy hybrid resinbased carbon fiber-reinforced polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The carbon fibres, polyamide 6 matrix, PUD surface treating agents, fabric treating procedures and fabricating processes of the CF/PA6 laminates investigated in the present study were basically same to those reported in Refs. [5, 6]. In detail, a commercial carbon cloth (TC33-3K) in plain-woven structure from Formosa Plastic Corporation (Taipei, Taiwan) was used as reinforcement, which contained 50 (warp) 50 (weft) bundles (fineness of warp and weft yarns: 200 tex) per 10 10 cm 2 area.…”
Section: Methodsmentioning
confidence: 99%
“…Polymer composites are composed of various reinforcements and matrix systems, hence the mechanical properties are mainly influenced by reinforcements/matrix properties, reinforced forms, the surface morphology of reinforcement, impregnation condition and also interfacial bonding capability between reinforcements and matrix [3][4][5][6][7][8]. There are lots of methods to improve the impregnation condition and interfacial bonding capability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations